Analisis Proses Pembakaran Pada Motor Vario 124.8 cc Menggunakan Simulasi ANSYS - Achmad Budi Ramadhan; Angga Reyvaldi Pradana; Hidayat Pratama; Iqbal Setyawan (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In the development of technology, it can facilitate testing and experiments that will be conducted. By using the available technology, it can reduce costs and time efficiency in conducting research and experiments. The simulation of the combustion process of the 124.8cc Vario motor includes an analysis of the process, temperature, pressure, and crankshaft angle in the combustion of the motor. The purpose of this simulation is to determine when the combustion starts, the final combustion angle produced if the RPM increases, the pressure generated when the RPM increases, and the peak temperature when the RPM increases. This simulation was performed using Ansys 2023 R1 software.